Glucomannan–xylan blend biofilms for food packaging: preparation and evaluation of filmogenic solutions and biofilms - Al-Ajlouni, Khaloud; Fleming, Paul; Pekarovicova, Alexandra (Journal of Print and Media Technology Research, 2022)
Food packaging nowadays requires a sustainable, biodegradable, and friendly to the environment wrapping films. After cellulose, the hemicellulose in plants and grasses is the potential source for the biofilms. Konjac glucomannan is one of the hemicelluloses used to synthesize wrapping films. In this research, we conducted three sets of experiments: we formulated pure glucomannan biofilms, glucomannan–xylan blend biofilms with nano-fibrillated cellulose (NFC), and finally glucomannan–xylan blends without NFC. We studied the rheology of the filmogenic solution of the blends, before casting, and the physical and mechanical properties of the biofilms. The biofilms consisted from: glucomannan, xylan, NFC as reinforcement polymer, Surfynol 104 PA as surfactant and Sorbitol as a plasticizer. Pure glucomannan was stiff and viscous and in some cases showed a faceting phenomenon. In general, blended biofilms exhibited better properties with the presence of NFC in the formulation.